2005
DOI: 10.1103/physrevd.71.077502
|View full text |Cite
|
Sign up to set email alerts
|

Measure of the path integral in lattice gauge theory

Abstract: We show how to construct the measure of the path integral in lattice gauge theory. This measure contains a factor beyond the standard Haar measure. Such factor becomes relevant for the calculation of a single transition amplitude (in contrast to the calculation of ratios of amplitudes). Single amplitudes are required for computation of the partition function and the free energy. For U (1 ) lattice gauge theory, we present a numerical simulation of the transition amplitude comparing the path integral with the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The effective interaction terms in the Lagrangian which appear due to the presence of the Haar measure have been discussed earlier in QCD (see [43] and references therein).…”
Section: B Pion Field Parameterization In Chiral Sigma Modelmentioning
confidence: 99%
“…The effective interaction terms in the Lagrangian which appear due to the presence of the Haar measure have been discussed earlier in QCD (see [43] and references therein).…”
Section: B Pion Field Parameterization In Chiral Sigma Modelmentioning
confidence: 99%
“…(35) goes over to δ(U fi − U in ), as should be. A numerical simulation [47] has shown that in lattice gauge theory (with non-zero a 0 ) also the sub-leading term is important and can not be neglected.…”
Section: U(1) 2+1 Lattice Gauge Theorymentioning
confidence: 99%
“…In the case of U(1) lattice gauge theory, such normalization factor has been computed in Ref. [47]. It is given as follows.…”
Section: U(1) 2+1 Lattice Gauge Theorymentioning
confidence: 99%